2020
DOI: 10.1080/10439463.2020.1776280
|View full text |Cite
|
Sign up to set email alerts
|

Community oriented policing theory and practice: global policy diffusion or local appropriation?

Abstract: Latin America and the Caribbean (LAC) have now had 20 years of experience with community policing programmes (COP), yet high rates of public crime and violence, police violence and corruption, as well as public distrust of the police continue. The introduction to this special issue frames a set of contributions that, together, tell the story of COP's problems and promise in the region. It argues that, in Latin America and the Caribbean, COP is often locally and regionally (mis)appropriated in ways that challen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 49 publications
0
8
0
1
Order By: Relevance
“…Evaluations of this model in the global North have produced mixed results (BULLOCK, 2013;MCCARTHY, PORTER, TOWNSLEY and ALPERT, 2020), it remains difficult to establish the actual reach and success of the model in Latin America. On one hand, some studies on the Latin American experience have demonstrated serious attempts to change police institutions, albeit without much success (FRÜHLING, 2012), while others have shown the existence of many local variations that have distanced themselves from the principles of the Anglo-Saxon model (DIAS FELIX and HILGERS, 2020;DAMMERT and CASTAÑEDA, 2019). Many attempts to implement this approach have only focused on enhancing image of the police (FRÜHLING, 2012), and have prevented advancements toward more democratic police models in the region.…”
Section: Crime Prevention and Community Police In Latin Americamentioning
confidence: 99%
“…Evaluations of this model in the global North have produced mixed results (BULLOCK, 2013;MCCARTHY, PORTER, TOWNSLEY and ALPERT, 2020), it remains difficult to establish the actual reach and success of the model in Latin America. On one hand, some studies on the Latin American experience have demonstrated serious attempts to change police institutions, albeit without much success (FRÜHLING, 2012), while others have shown the existence of many local variations that have distanced themselves from the principles of the Anglo-Saxon model (DIAS FELIX and HILGERS, 2020;DAMMERT and CASTAÑEDA, 2019). Many attempts to implement this approach have only focused on enhancing image of the police (FRÜHLING, 2012), and have prevented advancements toward more democratic police models in the region.…”
Section: Crime Prevention and Community Police In Latin Americamentioning
confidence: 99%
“…Community policing (COP) is a strategy developed and adopted with the specific goal of improving conditions of trust between the police and public. Its modern roots lie in the United States in the 1970s [10,15,16], from where it spread into Canada and Europe, and on into Latin America, Africa, and Asia. Although Bayley [17] argues that there is no agreed definition of COP there appear to be similar conditions [18] for its testing and implementation i.e., it is a clear effort to respond to a lack of public confidence in the police.…”
Section: Community Policing and Trust In The Police In Post-conflict ...mentioning
confidence: 99%
“…Key sources on COP have focused on its impact, concluding that there is significant evidence that this strategy for policing improves local citizens perceptions of the police, their approval of their activities, their legitimacy as a state institution, but it has some limited impact on the levels of crime and related fears [22]. In Latin America there are studies which focus on conditions for COP success [23], as well as on problems of implementation [10,[24][25][26].…”
Section: Community Policing and Trust In The Police In Post-conflict ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Enhanced capacities for crime investigation have promoted professionalization within the police that open up possibilities to consolidate a preventive approach to security by developing its capacities for community-oriented policing. COP means different things in different contexts but can generally be conceptualized as "full-service personalized policing where the same officer patrols and works in the same area on a permanent basis, from a decentralized place, working in a proactive partnership with citizens to identify and solve problems" [12,13]. It can generally be considered functional to police reform in that it "marks a shift in emphasis [...] from reactive to preventive policing [...], from the police as representing external coercion to police embedded in and working in partnership with communities" [13].…”
Section: Community Oriented Policing As An Opportunity To Further Polmentioning
confidence: 99%